Modelling coils system for generating homogeneous magnetic field; IOP Conference Series: Materials Science and Engineering; Vol. 66: 20th International Conference for Students and Young Scientists: Modern Techniques and Technologies (MTT'2014), Tomsk, Russia, 14-18 April 2014 - Ogay V. E. Vitaliya Evgenyevna (2014, 2014)
Title screen